Expressão dos receptores A1 e A2a de adenosina no desenvolvimento e após plasticidade induzida no colículo superior de ratos - Gomes, Ana Lúcia Tavares (2009)
The retinotectal projection of rats develops within the two/three post-natal weeks. During this critical period, rapid reorganization in this pathway can be induced by lesions or manipulations that interfere with the pattern of electrical activity, release of retrograde messengers or neurotransmitters. Adenosine is a neuromodulator implicated in nervous system development and plasticity. Here we investigated the expression of A1 and A2a receptors in the normal develoment of superior colliculus and after monocular enucleation at postnatal day 10 or 21 (PND10/21). We also examined the localization of imunoreactivities cells to A2a receptors in the superior colliculus at different stages of normal development. Lister Hooded rats ranging from PND0 to PND70 were used for ontogeny studies. Animals submitted to monocular enucleation received a survival-time ranging from 3 hours to six months post-lesion. For both groups, tissue homogenization and protein extraction were performed and processed for western blotting. A group of animals were perfused transcardially with saline and aldehydes and the sections processed for immunohistochemistry studies. Our data showed that A1 expression is higher during early postnatal development while A2a expression has an opposite developmental pattern. The immunohistochemistry revealed not only an increase in the density of A2a receptor immunolabel throughout the development of the superior colliculus but also that A2a is expressed both in pre- and post-synaptic cells. Monocular enucleation induced modifications in both A1 and A2a expression at denervated colliculus. Taken together, the results suggest a balance of purinergic A1 and A2a signalling that play a role in retinotectal development and also that the lesion-induced plasticity could be modulate by alterations in the purinergic system.